Design and stiffness analysis of A class of 2-DoF tendon driven parallel kinematic mechanism - Ma, Nan; Yu, Jingjun; Dong, Xin; Axinte, Dragos A. (Elsevier, 2018)
2-DoF Rotational mechanism is increasingly utilized in a large range of industrial applications. However, the structures of most of the existing mechanisms are very complex, which is a significant challenge for building them, due to the tight tolerance and assembly difficulties. In this paper, a class of 2-DoF tendon driven parallel kinematics mechanisms (TDPKM) are introduced, which can be structured with low manufacturing and assembly difficulties and is able to actively adjust the system stiffness. Since the unique class of mechanisms is developed, the kinematic model is established to derive the stiffness model, which considers the tendon, structural and central joint stiffness. Finally, a set of experiments of the deviation measurement under different payloads within the workspace are implemented and compared with the theoretical calculations presented in this paper. The overall deviation error between the experimental test and theoretical calculation are between 0.9% and 4.7% in the whole workspace.